Case-Control Study: Risk Factors for Diarrhea in Toddlers in the Doro 1 Community Health Center Work Area - Risqiyanti, Eva; Lailis Sa'adah; Adinda Zahra Nur Maulida; Jaya Maulana; Dewi Nugraheni Restu Mastuti (LPPM Universitas Pekalongan, 2025)
The significant rise in diarrhea cases in the highland area of ​​Puskesmas Doro 1, reaching 339 cases in 2025. This study employed a mixed-methods design with a sequential explanatory model. The quantitative phase used a case-control study on 34 toddlers (17 cases and 17 controls) selected through consecutive and simple random sampling. Data analysis utilized the Chi-Square test. The qualitative phase involved in-depth interviews with policymakers. The results showed a significant relationship between diarrhea incidence and clean water facilities (p=0.001; OR=35.00), family latrines (p=0.002; OR=10.56), and waste disposal facilities (p=0.016; OR=5.76). On the other hand, parenting style and handwashing with soap (CTPS) showed no significant relationship. Qualitative findings confirmed that water source contamination due to substandard septic tank distances was the primary cause, even though community hygiene behavior was adequate. Poor physical environmental quality is the major determinant of diarrhea incidence compared to behavioral factors. Interventions focusing on improving basic sanitation infrastructure and protecting water sources are required to break the chain of transmission. Keywords: Case-Control, Toddler Diarrhea, Environment, Mixed Methods, Risk Factors